Pengaruh Kampanye Hijau “Tumblr Day” terhadap Minat Beli Melalui Brand Trust pada Konsumen Starbucks Coffee (Studi Kasus pada Konsumen Starbucks Coffee di Kota Bandung) - Nabilaah, Jihan; Nurtjahjadi, Edi (Universitas Batanghari, 2024)
The development of the business world in Indonesia is growing, seeing more and more types of businesses and industries emerging, one of which is in the food and beverage sector. Apart from that, the trend of drinking coffee is also increasing. However, the percentage index for Starbucks Coffee experienced a decline in the 2021-2023 period, while its competitors actually experienced an increase in the same year period. This indicates a decrease in buying interest in Starbucks Coffee. The aim of this research is to determine the effect of the green campaign